Polymorphisms in the apoptotic pathway gene BCL-2 and survival in small cell lung cancer - Knöfel, Lena Franziska; Werle-Schneider, Gisela; Dally, Heike; Müller, Phillip; Edler, Lutz; Bartsch, Helmut; Tuengerthal, Siegfried; Heußel, Claus Peter; Reinmuth, Niels; Thomas, Michael; Risch, Angela (Journal of thoracic oncology, 2011)
Introduction: - We investigated the single-nucleotide polymorphism C-938A in the apoptotic gene BCL-2 to assess the potential impact as a genetic marker for response to chemotherapy and outcome prediction in small cell lung cancer (SCLC) patients. Such a marker might help optimize lung cancer treatment in a tailored approach. - Methods: - DNA derived from peripheral blood lymphocytes of 188 Caucasian SCLC patients treated at the Thoraxklinik Heidelberg was genotyped. Chemotherapy response, time to progression (TTP), and overall survival (OS) were evaluated using multivariable regression (unconditional logistic for response and Cox proportional hazard for TTP and OS) with odds ratios and hazard ratios (HRs) and their 95% confidence intervals (CIs) as quantitative outcome measures, respectively. - Results: - Small cell lung cancer patients carrying the BCL-2 -938CC genotype showed significantly worse TTP than patients carrying the BCL-2 -938AA genotype (HR = 1.86; 95% CI = 1.10-3.13, p = 0.021). The same adverse effect was shown for OS (HR = 2.38; 95% CI = 1.38-4.12, p = 0.002). Also, patients with limited disease (HR = 2.57; 95% CI = 1.18-5.60, p = 0.017) showed worse OS with the BCL-2 -938CC genotype. - Conclusion: - BCL-2 -938CC genotype shows significantly worse outcome in small cell lung cancer patients. This genetic marker might particularly impact on treatment strategies using BCL-2 antisense approaches.